Hematological characteristics and hepatobiliary complications of hereditary spherocytosis in a tertiary care pediatric center: optimizing diagnosis and care through local and international networks - Boaro, Maria Paola; Reggiani, Giulia; D’Agnolo, Mirco; Munaretto, Vania; Pozzebon, Francesco; Trapanese, Roberta; Martella, Maddalena; Colombatti, Raffaella (Frontiers in Pediatrics, 2023)
Background Hereditary Spherocytosis (HS) is a rare, congenital red blood cell disorder presenting with variable clinical manifestations ranging from mild hemolytic anemia to severe anemia with hypersplenism and hepatobiliary complications. Methods The objectives of the study were to evaluate the diagnostic pathway of HS, the presence and management of hepatobiliary complications in pediatric patients with HS followed in a tertiary care center. The demographic, clinical, hematological information were retrieved from medical records of patients having at least 1 hematology visit between 2010 and 2020. Results Forty-two patients were enrolled, 23 M. Mean age at onset of symptoms was 2.8 years, at diagnosis was 3.5 years. Anemia was the first manifestation in 73%; suspect of HS arose for all patients in first or second level outpatient clinics. Only 64% of patients performed two confirmation tests in the reference center. 28/42 had familiarity for HS; of the 13/42 who did not, only 47% performed further analysis. Sixteen patients developed gallbladder stones (40%), visible at the first ultrasound (5.6 years). Hemolytic crises and parvovirus infections were more frequent in patients with stones (53.6% vs. 26.1% and 63.6% vs. 28.6%, respectively). 10/16 (62.5%) underwent elective cholecystectomy: 8 had concomitant splenectomy. Conclusions our study highlights the need to optimize the diagnostic pathway in networks of care involving general and specialized centers in order to reduce time to diagnosis and ensure that all patients receive confirmatory tests. A high frequency of hepatobiliary complications since young age was observed suggesting that screening with ultrasound should begin earlier